2007
DOI: 10.1016/j.lfs.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ICV administration of the alpha1A-adrenoceptor antagonist 5-methylurapidil on concurrent measures of eating and locomotion after cocaine in the rat

Abstract: Psychostimulants including amphetamine and cocaine induce locomotion and stereotypy and suppress eating. Although the capacity of cocaine to alter locomotion is usually viewed as related to dopamine neurotransmission, recent studies suggest that norepinephrine, acting through alpha1-adrenergic receptors (alpha1-ARs) can facilitate cocaine-stimulated locomotion. Of the three alpha1-AR subtypes (alpha(1A), alpha(1B), and alpha(1D)) identified to date, inactivation of the alpha(1B)-AR subtype diminishes cocaine-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Because recent studies have shown that MC4R signaling in the NAc is required for certain behavioral responses to cocaine- (Hsu et al 2005) and stress-induced anhedonia, hypophagia and body weight loss (Lim et al 2012), we speculated that MC4R signaling in D1R neurons might suppress food intake under specific conditions. To test this hypothesis, we determined the effect of cocaine, which potently suppresses appetite (Clifford et al 2007;Wellman et al 2002), on food intake in our mouse models. An acute IP injection of cocaine (15 mg/kg) induced a significant suppression of food intake in the control and MC4R/D1R groups Genes, Brain and Behavior (2013) after 4 h (one-way ANOVA followed by Tukey's post hoc analysis, F 2,23 = 5.925, P = 0.0084, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because recent studies have shown that MC4R signaling in the NAc is required for certain behavioral responses to cocaine- (Hsu et al 2005) and stress-induced anhedonia, hypophagia and body weight loss (Lim et al 2012), we speculated that MC4R signaling in D1R neurons might suppress food intake under specific conditions. To test this hypothesis, we determined the effect of cocaine, which potently suppresses appetite (Clifford et al 2007;Wellman et al 2002), on food intake in our mouse models. An acute IP injection of cocaine (15 mg/kg) induced a significant suppression of food intake in the control and MC4R/D1R groups Genes, Brain and Behavior (2013) after 4 h (one-way ANOVA followed by Tukey's post hoc analysis, F 2,23 = 5.925, P = 0.0084, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, spontaneous wheel running and novelty-induced rearing were also reduced in these animals, indicating a nonspecific effect on motor activity (Sadalge et al, 2003). Intracerebroventricular administration of the a1a receptor antagonist, 5-methylurapidil, failed to suppress cocaine hyperlocomotion (Clifford et al, 2007). The location of the a1ARs regulating stimulant-induced activity appears to be the prefrontal cortex (PFC; Blanc et al, 1994;Darracq et al, 1998) and nucleus accumbens shell (Mitrano et al, 2012), because local infusions of a1AR antagonists into these regions reduced cocaine and/or amphetamineinduced locomotion.…”
Section: Stimulant-induced Locomotor Activitymentioning
confidence: 91%
“…5-HT1B and 5-HT2C mediate satiety, while 5-HT6 antagonists reduce food intake [161]. Cocaine was found to suppress eating; this was not affected by a NE antagonist, which by itself, stimulated eating [162]. The specificity of food reward is indicated by such findings as a glutamate antagonist reduces amphetamine but not food reward [163].…”
Section: Components Of Food Rewardmentioning
confidence: 99%